1976
DOI: 10.1111/j.1476-5381.1976.tb07472.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Experimental Diabetes, Food Deprivation and Genetic Obesity on the Sensitivity of Pithed Rats to Autonomic Agents

Abstract: I The sensitivities of alloxan and streptozotocin diabetic and hereditary obese pithed rats to acetylcholine, isoprenaline and noradrenaline were compared to those of controls. 2 Blood pressure and heart rate recordings made before dosing was started showed the streptozotocin-treated animals to have a significantly reduced heart rate and increased pulse pressure as compared with controls.3 Both diabetic groups were found to have reduced sensitivities to the pressor effect of noradrenaline, the depressor effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

1980
1980
2004
2004

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(28 citation statements)
references
References 18 publications
2
26
0
Order By: Relevance
“…Both hypertensive and normo tensive diabetic animals exhibited significantly reduced pressor responses in comparison to their age-matched controls. Foy and Lucas (17), using pithed normotensive rats only 1 week after alloxan, found similar reductions in vascular sensitivity to vasoactive agents. On the other hand, responses of the isolated atrial and aortic preparations taken from diabetic WKY and control preparations were not readily dis sociable.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Both hypertensive and normo tensive diabetic animals exhibited significantly reduced pressor responses in comparison to their age-matched controls. Foy and Lucas (17), using pithed normotensive rats only 1 week after alloxan, found similar reductions in vascular sensitivity to vasoactive agents. On the other hand, responses of the isolated atrial and aortic preparations taken from diabetic WKY and control preparations were not readily dis sociable.…”
Section: Discussionmentioning
confidence: 87%
“…Placing the tissues in fresh physiological solution may restore them to a more normal environment, by washing out toxic metabolites or by avoiding impaired metabolic pathways. Foy and Lucas (17) have suggested that hyperglycemia per se may be one cause of the reduced sensitivity, since starvation of subsequently pithed diabetic rats normalized the responses to various vasoactive agents. In addition, Malik and McGiff (28), using high glucose perfusate, have reported reductions in constrictor responses in perfused rat mesen teries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Foy and Lucas (1 976) demonstrated that the chronotropic response of both alloxan (1 week) and ' control rats. In direct contrast, these authors obsened an increase in the chronotropic response of isolated spontaneously beating right atria from streptozotocin-diabetic rats (2 weeks) to both norepinephrine and isoproterenol (Foy and Lucas 1978). Ingebretsen et al (1980) observed no difference in the inotropic response of isolated working hearts from alloxan-diabetic (72 h) rats to isoproterenol.…”
Section: Introductionmentioning
confidence: 92%
“…4 The depressed blood pressure and pacemaker function (heart contractility) we observed over the 21 dayonset of diabetes were previously reported in this rat model for up to 6-7 weeks. [14][15][16][17][18][19] Thus, the prevalence of hypertension in the diabetic population, an important risk factor for atherosclerosis, is not met in such a short period of time. Indeed, chronic hypertension in the STZ rat model was only observed after diabetes had been present for 20 weeks.…”
Section: Discussionmentioning
confidence: 99%